2019
DOI: 10.3390/polym11050862
|View full text |Cite
|
Sign up to set email alerts
|

Semi-Interpenetrating Polymer Networks Based on Cyanate Ester and Highly Soluble Thermoplastic Polyimide

Abstract: Thermoplastic polyimide (TPI) was synthesized via a traditional one-step method using 2,3,3′,4′-biphenyltetracarboxylic dianhydride (3,4′-BPDA), 4,4′-oxydianiline (4,4′-ODA), and 2,2′-bis(trifluoromethyl)benzidine (TFMB) as the monomers. A series of semi-interpenetrating polymer networks (semi-IPNs) were produced by dissolving TPI in bisphenol A dicyanate (BADCy), followed by curing at elevated temperatures. The curing reactions of BADCy were accelerated by TPI in the blends, reflected by lower curing temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…Liu et al [ 42 ] reported the synthesis of semi-IPN by blending epoxy (BADCy) and thermoplastic polyimide (TPI) without any addition of solvent. The prepared blends displayed improved processability, as compared to the neat epoxy, as shown by the reduction in gelation time at 200 °C and lower values of viscosity onset temperature.…”
Section: Ipn Based Epoxy Systems With Thermoplastic Toughenersmentioning
confidence: 99%
“…Liu et al [ 42 ] reported the synthesis of semi-IPN by blending epoxy (BADCy) and thermoplastic polyimide (TPI) without any addition of solvent. The prepared blends displayed improved processability, as compared to the neat epoxy, as shown by the reduction in gelation time at 200 °C and lower values of viscosity onset temperature.…”
Section: Ipn Based Epoxy Systems With Thermoplastic Toughenersmentioning
confidence: 99%
“…The first is to blend a thermoplastic polymer with a thermoset resin. [18,21] However, most of the thermoplastic polymers used in this method have a considerable effect on the overall viscosity properties of the blends and also cause poor adhesion at the interface between thermoplastic and thermoset resin. [21][22][23] The second method is to introduce a block copolymer into the CE.…”
Section: Introductionmentioning
confidence: 99%
“…[18,21] However, most of the thermoplastic polymers used in this method have a considerable effect on the overall viscosity properties of the blends and also cause poor adhesion at the interface between thermoplastic and thermoset resin. [21][22][23] The second method is to introduce a block copolymer into the CE. [19] One end of the molecular chain of the designed block copolymer is connected to the cyanate resin, and the other end is connected to a group incompatible with the cyanate resin.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, most of the experiments and simulations take polymer solution as the research object and there is less research on ASP solution. And most of the experimental research methods for polymer and other displacement agents are mainly aimed at analyzing the characteristic structure of molecular micromorphology [34,35,36,37] and the relevant parameters of shear rheological experiments [38,39,40,41,42,43,44,45,46,47,48]. Such research methods are relatively single.…”
Section: Introductionmentioning
confidence: 99%